Paiement Pour Services Ecosystemiques, Instrument D’incitation Au Developpement Des Jardins Publics Et Prives Dans Les Communes De Cocody Et Du Plateau (Abidjan – Côte d’Ivoire) - Kouadio, Yao Jean-Clovis; Ouattara, Djakalia; Tiébré, Marie-Solange; Oulaïtar, Monssou Eugène; Nomel, Richard; N’Guessan, Kouakou Edouard (European Scientific Journal, ESJ, 2018)
The public and private green spaces of the communes of Cocody and Plateau of Abidjan city are deteriorating because of lack of financial means for their maintenance. The overall objective of this study is to demonstrate the importance of payments for ecosystem services (PES) in their self-financing. To carry out this study, a survey was conducted among users of 3 public gardens in the Plateau and private garden owners in Cocody. It aimed to identify the willingness to pay (CAP) of users of public gardens for their management and to identify incentives for the creation of private gardens in their own concessions. Analysis of the data reveals a PAC in the form of visiting tax or voluntary donation ranging from 100 FCFA (0.15 €) to 2000 FCFA (3.07 €). Respondents who declare a visiting tax between 100 FCFA and 500 FCFA are the most numerous with a percentage of 92.95. Students, students and unemployed visitors are on the sidelines of visitors who refuse to pay for the management of public gardens. If we stick to the visit fees proposed by the majority of the interviewees, it would be possible to collect 79,800 FCFA (122.76 €) per day for 339,000 FCFA (521.53 €) for all 3 public gardens. With regard to the creation of private gardens, a financial subsidy mechanism could motivate the population. This study demonstrates that the introduction of payments for ecosystem services could be an incentive for the development of green spaces in urban areas.